Peroxisomal Membrane Protein PMP34 Is Involved in the Human Papillomavirus Infection Pathway - Ito, Rie; Kitamura, Koji; Inohara, Hidenori; Yusa, Kosuke; Kaneda, Yasufumi; Nimura, Keisuke (Frontiers in Virology, 2022)
Infection with high-risk human papillomavirus (HPV) types is linked to the onset of several cancers. The mechanism of HPV infection, however, has not yet been fully elucidated. Here, using the newly developed HPV infectious pseudovirion (HPV PsV) and a genome-wide clustered regularly interspaced short palindromic repeat (CRISPR) screening system, we established an experimental system and searched for genes involved in HPV infection. The HPV PsV has the truncated herpes simplex virus thymidine kinase (dTK) to kill PsV-infected cells when combined with ganciclovir. The five rounds of selection of 293FT cells by infection with HPV PsVs identified two candidate genes involved in the HPV infection pathway. The validation experiments showed that SLC25A17, which encodes the peroxisomal membrane protein PMP34, was involved in the HPV infection pathway. The gRNAs against SLC25A17 attenuated the efficiency of HPV PsV infection in 293FT and HeLa cells. Although further experiments are required to determine whether PMP34 acts as a receptor for HPV, these results indicate that our screening system is useful for identification of the genes involved in the HPV infection pathway.